The Influence of Promotion and Perceived Trust on Purchase Intention in Beauty Product E-Commerce - Thamanda, Dhea Rusli; Mariam, Siti; Ramli, Abdul Haeba (LPPM Institut Bisnis dan Informatika Kesatuan, 2024)
This study is a quantitative study to determine the direct influence between promotion, attitude, perception of trust, perception of ease of use, perception of usefulness on purchase intention on Sociolla e-commerce. Data collection in this study was conducted through a survey with a questionnaire in the form of a google form. The population in this study were Sociolla e-commerce consumers who live in the province of DKI Jakarta, have made transactions more than twice and are 17 years of age and over. The questionnaires collected amounted to 135 respondents using the formula (Hair et al., 2020). Sampling used a purposive sampling technique, then the data was processed using a multiple regression analysis method. Based on the results of the study, from the 5 hypotheses accepted, namely promotion has a positive effect on purchase intention, attitude has a positive effect on purchase intention, perception of trust has a positive effect on purchase intention, perception of ease of use has a positive effect on purchase intention, perception of benefits does not have a positive effect on purchase intention. The results of this study are expected to provide input for beauty product e-commerce to better understand customer needs and continue to develop better digital sales strategies to help consumers in their shopping activities. Keywords: Promotion, Attitude, Perceived Trust, Perceived Ease of Use, Perceived Usefulness, Purchase Intention.